Предмет: Химия,
автор: plevakoillya
6) Fe2O3 → FeCl3 -> Fe(NO3)3 – Fe(OH)3 - Fe2(SO4)3
Ответы
Автор ответа:
1
Объяснение:
1)FeCl3+3HNO3=Fe(NO3)3+3HCl
2)2Fe(NO3)3+3H2SO4=Fe2(SO4)3+6HNO3
3)Fe2(SO4)3+6NaOH=2Fe(OH)3+3Na2SO4
4)2Fe(OH)3=Fe2O3+3H2O
5)2Fe2O3=4Fe+3O2
Автор ответа:
1
Fe2O3 + 6HCl = 2FeCl3 + 3H2O
FeCl3 + 3AgNO3 = 3AgCl + Fe(NO3)3
Fe(NO3)3 + 3NaOH = 3NaNO3 + Fe(OH)3
2Fe(OH)3+3H2SO4=Fe2(SO4)3+6H20
Похожие вопросы
Предмет: Русский язык,
автор: жүзім
Предмет: Английский язык,
автор: Марина5051
Предмет: Русский язык,
автор: Mark3Oleg
Предмет: Українська мова,
автор: irinanovikova221
Предмет: Алгебра,
автор: alinadamaeva200